Quality Assurance & Quality Control of Environmental Field Samples. - Zhang, Chunlong (Future science., 2014)
The ten chapters of this book provide comprehensive coverage of quality issues in environmental sampling, addressing recent developments and research advances together with advice based on the contributing experts' practical experience.